HUBUNGAN INTENSITAS MEMBACA AL-QUR’AN DENGAN KECERDASAN EMOSIONAL MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SEMARANG - Muhammad Danil Ramadhan; Wijayanti Fuad; Rochman Basuki (PT. Hasba Edukasi Mandiri, 2026)
The Relationship of the Intensity of Reading the Qur’an with the Emotional Intelligence of Students of the Faculty of Medical Muhammadiyah University Semarang. Students' failure to control emotional turmoil is caused by a lack of emotional intelligence. 2019 Centers For Disease Control data shows that in the United States in 2016-2019, 32.5% of students experienced emotional problems. In Indonesia in 2013-2018, the prevalence of emotional intelligence was still low, namely 9.8%. One of the factors that influences emotional intelligence is reading the Koran. Reading the Qur'an is an effort made to change behavior, control morals, and develop morals. This study aims to analyze the relationship between the intensity of reading the Al-Qur'an and the emotional intelligence of students at the Faculty of Medicine, Muhammadiyah University, Semarang. This research is a quantitative study with a cross sectional approach on 67 students of the UNIMUS Faculty of Medicine, even semester class of 2023. Sampling used a simple random sampling technique by filling out the Al-Qur'an Reading Intensity questionnaire and the Emotional Intelligence questionnaire. Correlation analysis uses the Spearman rank test. There is a significant relationship between the intensity of reading the Qur’an and emotional intelligence p-value = 0.000 (<0.05) and the correlation coefficient (r) is (+0.642). There is a relationship between the intensity of reading the Al-Qur'an and the emotional intelligence of students at the Faculty of Medicine, Muhammadiyah University, Semarang, with a strong relationship strength and a positive correlation direction (+). The higher the intensity of reading the Qur’an, the higher the Emotional Intelligence.